Oral vinorelbine plus cisplatin as first-line chemotherapy in nonsquamous non-small-cell lung cancer: final results of an International randomized phase II study (NAVotrial 01) - Bennouna, Jaafar; Havel, Libor; Krzakowski, Maciej; Kollmeier, Jens; Gervais, Radj; Dansin, Eric; Serke, Monika; Favaretto, Adolfo; Szczesna, Aleksandra; Cobo, Manuel; Ciuffreda, Libero; Jassem, Jacek; et al. (Clinical lung cancer, 2014)
BACKGROUND: The combination of oral vinorelbine plus cisplatin has been studied in numerous trials as first-line treatment of patients with non-small cell lung cancer (NSCLC) regardless of histologic subtype. NAVoTrial 01 is the first study that explores this combination specifically in nonsquamous (NS) NSCLC by assessing the feasibility of this doublet (ratio 1:2) in an investigational approach. A reference arm with pemetrexed plus cisplatin was included. Maintenance therapy with single-agent therapy after 4 cycles of combination therapy was included in the study schedules because it reflected a trend in first-line treatment of NSCLC. PATIENTS AND METHODS: Stage IIIB/IV untreated/relapsed patients with NS NSCLC received a 3-week cycle of pemetrexed 500 mg/m(2) and cisplatin 75 mg/m(2) on day 1 (arm A) or oral vinorelbine 80 mg/m(2) on days 1 and 8 (first cycle 60 mg/m(2)) and cisplatin 80 mg/m(2) on day 1 (arm B). After 4 cycles, patients without disease progression received single-agent maintenance treatment with pemetrexed or oral vinorelbine. RESULTS: Overall, 153 patients were randomized (arm A/arm B: 51/102). Disease control rate (%) for arm A was 76.5 (95% confidence interval [CI], 62.5-87.2) and for arm B it was 75.0 (95% CI, 65.3-83.1), Response rates for arm A were 31.4% (95% CI, 19.1-45.9) and for arm B were 24.0% (95% CI, 16.0-33.6). Median progression-free survival for arm A was 4.3 months (95% CI, 3.8-5.6) and for arm B it was 4.2 months (95% CI, 3.6-4.7). Median survival for arm A was 10.8 months (95% CI, 7.0-16.4) and for arm B it was 10.2 months (95% CI, 7.8-11.9). Main grade 3/4 hematologic toxicities were neutropenia 18.3% (arm A) and 44.0% (arm B), whereas febrile neutropenia was reported in 2% of patients in each arm. CONCLUSION: Oral vinorelbine and cisplatin had an efficacy in line with that achieved with a standard treatment such as pemetrexed and cisplatin, coupled with an acceptable safety profile.
Keywords: guanin; cisplatina; Female; Advanced non–small-cell lung cancer; Neutropenia; Nonsquamous histologic subtype; glutamáty; Glutamates; nemalobuněčný karcinom plic; Cisplatin; ženské pohlaví; vinorelbin; nádory plic; lidé; Survival Analysis; staging nádorů; neutropenie; Chemotherapy; Antineoplastic Combined Chemotherapy Protocols; Vinorelbine; International Cooperation; protokoly protinádorové kombinované chemoterapie; Male; progrese nemoci; Aged; Carcinoma, Non-Small-Cell Lung; aplikace orální; Disease Progression; pemetrexed; analýza přežití; Lung Neoplasms; Guanine; Pemetrexed; lidé středního věku; mezinárodní spolupráce; senioři; mužské pohlaví; Administration, Oral; vinblastin; Middle Aged; Neoplasm Staging; Vinblastine; Humans